Peningkatan Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila dengan Model Discovery Learning di Kelas IV SDN 05 Payakumbuh - Dwifarzah, Daranda; Zuardi, Zuardi (Lembaga Yasin AlSys, 2025)
The low academic performance of students and the suboptimal implementation of Pancasila Education by teachers form the basis for this study. The objective is to describe the improvement in learning outcomes in Pancasila Education through the application of the Discovery Learning model in Grade IV at SDN 05 Payakumbuh. This research is a Classroom Action Research (CAR) employing both qualitative and quantitative approaches, conducted over two cycles, Cycle I comprising two sessions and Cycle II one session, each encompassing the stages of planning, implementation, observation, and reflection. The study involved 24 fourth-grade students. Data were collected through observation of teaching modules, instructional implementation, and students' learning outcomes. The results indicate improvements in: (a) the quality of teaching modules, which increased from 84.71% (good) in Cycle I to 94.44% (very good) in Cycle II; (b) the implementation of learning activities, in both teacher and student aspects, which rose from 82.81% (good) to 93.75% (very good); and (c) the average student learning outcomes, which improved from 67.16 in Cycle I to 85.41 in Cycle II. These findings demonstrate that the Discovery Learning model effectively enhances learning outcomes in Pancasila Education at the elementary level and contributes to the overall improvement of instructional quality.